2017
DOI: 10.1007/s10514-017-9680-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-manipulation with a library of virtual guiding fixtures

Abstract: Virtual guiding fixtures constrain the movements of a robot to task-relevant trajectories, and have been successfully applied to, for instance, surgical and manufacturing tasks. Whereas previous work has considered guiding fixtures for single tasks, in this paper we propose a library of guiding fixtures for multiple tasks, and propose methods for 1) Creating and adding guides based on machine learning; 2) Selecting guides on-line based on probabilistic implementation of guiding fixtures; 3) Refining existing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
(43 reference statements)
0
30
0
Order By: Relevance
“…With respect to our work, the gripper orientation is fixed and autonomously controlled based on the selected grasp pose. Raiola et al [61] presented a set of virtual fixtures which they demonstrated in a pick-and-place industrial task. Completion time decreased by approximately 15% compared to standard teleoperation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With respect to our work, the gripper orientation is fixed and autonomously controlled based on the selected grasp pose. Raiola et al [61] presented a set of virtual fixtures which they demonstrated in a pick-and-place industrial task. Completion time decreased by approximately 15% compared to standard teleoperation.…”
Section: Discussionmentioning
confidence: 99%
“…A passive switching mechanisim allows the operator to safely switch from one target to another through virtual damping injection. A different approach is proposed in [47] for handling multi-target fixtures when controlling a serial manipulator. The authors implement a control scheme in which all fixtures are simultaneously active, but they are scaled according to the probability that their corresponding task is chosen.…”
Section: Multi-target Haptic Guidancementioning
confidence: 99%
See 2 more Smart Citations
“…The robots avoided the physical interaction with the human as long as possible, and when a physical interaction occurred, they remained in a compliant mode so that the force was ignored. Raiola et al [14] addressed the problem of learning virtual guiding fixtures, analogous to the use of a rule when drawing, in human-robot collaboration. Even though there was physical interaction during the task execution, the robot did not use the force based information while guiding the human.…”
Section: Related Workmentioning
confidence: 99%